THE EFFECT OF HYDOXYAPATITE XENOGRAFT OF HARUAN FISH (Channa striata) BONE ON THE NUMBER OF OSTEOBLAST AND OSTEOCLAST (In Vivo Study On Mandibular Bone of Male Guinea Pigs) - Novia Agustina; Irnamanda DH; Fransiska Uli Arta Panjaitan (Dentino : Jurnal Kedokteran Gigi, 2018)
Background: Periodontitis is an inflammation of the periodontium tissue caused by certain microorganisms. The condition it self is marked by alveolar bone damage. The repair of damaged alveolar bone requires a process of bone remodeling. To help the process of bone remodeling, a graft material from haruan fish bone is used. The haruan fish bone is a waste from industrial processing crackers that have not been used by the people of South Kalimantan. The fish bone has inorganic substances such as calcium and phosphate. Objective: To prove the effect of xenograft hydroxyapatite of haruan fish bone on the number of osteoblast and osteoclast in remodeling process of male marmot bone. Methods and materials: This study used a pure experimental study with posttest only control group design. This study used two treatment groups which were the treatment group using hydroxyapatite haruan fish bone and a negative control group using aquades. Results: The mean value of osteoblast cell number after given hydroxyapatite of haruan fish bone was 15,72 cells, which was higher than given aquades only with 5,08 cells. While the number of osteoclast after given hydroxyapatite of haruan fish bone was 6,72 cells. It was higher than the given aquades only group which results in 4,04 cells. The Independent T test showed a significant difference (p<0.05) between the hydroxyapatite of haruan fish bone group and the negative control group with osteoblast data where p = 0,000 and osteoclast data where p = 0,006. Conclusion: Giving hydroxyapatite ofharuan fish bone can increase the number of osteoblast and osteoclasts in the remodeling process of male marmot bone.